Student Adoption of a Non-Traditional Teaching Method in Accounting: How Previous Experience Impedes Willingness to Change - Irena Stejskalová; Lenka Komárková; Martina Bednářová; Pavel Štrach (Journal on Efficiency and Responsibility in Education and Science, 2019)
The research paper is concerned with a new teaching method consisting of real-life case study that is used in accountancy and its introduction at two universities. The research was carried out at universities that specialise in preparing students to become managers. The main focus of the study is to look at the different ways students might accept the new teaching method. We consider the utilisation of an active form of teaching, as opposed to a passive form which is a more prevalent form of the teaching of accountancy in the Czech Republic. Since the use of active forms of teaching brings a range of advantages, case studies are rarely used, we were interested to see the students’ reaction. The research was carried out during two consecutive academic years and main factors that were examined to assess the introduction of real-life case studies were country, gender and previous experience with accountancy education at secondary school. The results clearly pointed out that men accept the new way of teaching better than women. Students with previous experience perceived case studies negatively. The results of the study indicate that when introducing changes to teaching, the need to introduce the changes must be clarified appropriately.